The Impact of Esg on the Default Risk of Family Firms: International Evidence - Espinosa-Mendez, C (Elsevier Ltd, 2024)
This research is focused on studying the relationship between ESG performance and default risk of family firms. The sample consists of the 500 largest family firms worldwide (including all continents) for the period 2015–2021. This study shows a positive and a statistically significant relationship between ESG score and Z-score. This is confirmed for ESG environmental and ESG social scores. We include ownership concentration of family members as well as the percentage of family members in the board of directors. In the first case, we detect a non-linear relationship between ownership concentration and Z-score (inverted U shape) and for the second variable we find a negative relationship between the family participation in the board and Z-score. Finally, financial constraints of family firms reduce the impact of ESG score on Z-score. © 2023 Elsevier B.V.